Analisis Analisis Perencanaan Sumber Daya Manusia (SDM) Dalam Peningkatan Mutu Pendidikan Di Sma Muhammadiyah Selong - Masbullah; Salmi Yuniar Bahri (MAMEN: Jurnal Manajemen, 2022)
Human resources (HR) is the most important asset in an organization/company, especially in an educational institution, so it is very important that existing human resources can be planned as well as possible, in order to realize the goals of the organization/institution. There are many models of effective and efficient human resource planning, but effective and efficient human resource planning is not realized optimally, only imagination. Therefore, this study was conducted with the aim of analyzing human resource planning and finding solutions to problems that affect human resource planning at SMA Muhammadiyah Selong. This research is a qualitative descriptive research in the field. Technically data collection is done by interview, observation, and document study. After the data is collected, then classify, design and present the data according to their respective data types. Before the data is collected first and checked for validity. The results of this study indicate that human resource planning is carried out through programs, planning stages, including indicators or quality targets to be achieved as a process of improving education. The form of planning includes the arrangement of resources which includes the development of human resources, the development of the learning process, as well as increasing the capacity of human resources to improve the quality of education.